Energy-driven circular design in the built environment: rethinking architecture and infrastructure - Munonye, Williams Chibueze; Ajonye, George Oche (Frontiers in Sustainable Cities, 2025)
This study explores the integration of energy-driven circular design principles within the built environment, aiming to foster sustainable, low-carbon cities and buildings. Currently as urbanization accelerates and environmental concerns heighten, the need for circular economy practices that promote energy efficiency, resource optimization, and waste reduction becomes increasingly urgent. However, through exploring existing literature, the study identifies the importance of energy-efficient systems and circular design, highlighting innovative approaches such as renewable energy integration, adaptive reuse of materials, and building energy optimization. This paper also examines the barriers to widespread adoption of these principles, including technological, economic, and policy-related challenges. Through a multi-disciplinary perspective, this study proposes actionable strategies for overcoming these barriers, emphasizing the importance of collaboration between architects, engineers, policymakers, and industry stakeholders. The paper also discusses the role of digital tools, such as Building Information Modeling (BIM), in enhancing the implementation of circular economy practices in construction and renovation. In conclusion, the study reinforces the potential of energy-driven circular design to significantly reduce the environmental impact of the built environment, offering pathways to achieving climate resilience and sustainability goals in urban contexts.